John XXI, the Pope Philosopher and Physician–Scientist of Portuguese Origins Died of Crush Syndrome in 1277 - De Santo, Natale G. (Journal of religion and health, 2021)
The aim of this work is to refer on the death due to crush syndrome in 1277 of Pope John XXI, philosopher, logician, anatomist, physician scientist, university professor of medicine at the university of Siena and author of books adopted for nearly 4 centuries in universities in the Middle Ages. The Pope died crushed by the ceiling of his office which had been built in rush to meet his need for a quiet and warm place, his need of light and nature. There he attended to his duties of governing the church, studied fine theological questions, inspected the stars, made experiments and discussed with the renowned ophthalmologists who in those days made Viterbo the center of the study on vision. Following the fall of the ceiling of his apartment, John XXI was extracted alive from among the pieces of wood and stones. However, a few days after the disaster, he died in bad conditions (miserabiliter). He experienced a typical death due to crush syndrome which was described for the first time by Antonino D’Antona, following the Messina-Reggio Calabria 1908 earthquake. He was born (c. 1210-1220) in Lisbon as Pedro Hispano (Peter of Spain). He had regular trivium and quadrivium courses at the University of Paris under Albertus Magnus, a talented naturalist. He became Master of Arts, then studied medicine out of Paris (probably Montpellier or Salerno). He wrote three treatises (On the eye (De oculo), The Treasury of Medicines for the Poor (Thesaurus Pauperum) and Little Summaries of Logic (Summulae Logicales)) which were used in the European universities from the 13th to the beginning of the 18th century. Pedro Hispano was advisor of King Alphonso III for affairs inherent to the Church, bishop of Braga and then Cardinal Bishop of Tusculum and Pope as John XXI. He was buried in the Cathedral of Viterbo, the city where he had settled the seat of the Pontiff.